Enhanced ionized sputtering in HIPIMS. (4th October 2013) - Alami, Jones
Abstract The present paper aims to shortly review a relatively new approach to magnetron sputtering, namely "enhanced ionization sputtering" (EIS) or as it is more commonly known "High Power Pulsed Magnetron Sputtering" (HIPIMS). The EIS concept describes a range of plasmas that have the common features of exhibiting a higher (than what is commonly known) plasma density and a higher ionization fraction of sputtered and gas atoms in the discharge. The somewhat unique properties are the result of pulsing a sputtering source (target) power at a low frequency ranging from a few tens to a few hundreds of Hz and a low duty time of less than 10 %. Consequently, plasma electron densities 2 to 4 orders of magnitude higher than densities in conventional sputtering plasmas can be achieved, while the corresponding ionization fractions of the target material reach up to 90 % for Ti, for example. As will be shown in the present paper, EIS is described as an approach to sputtering that provides new means and a realm of possibilities to develop coating solutions not possible otherwise. This implies that there is not a single description of a HIPIMS plasma, rather a concept for ionization (EIS) that should be used according to the needs of the application in hand. Nevertheless, for the purpose of simplicity, HIPIMS should describe in the present paper both the concept and the technique.